(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The facies analysis and the study of the way of life of the organisms have been historically considered as the conventional methods for the study of the sedimentary environment and therefore for paleodepth estimations. The aim of this work is, first to rule out possible diagenetic alterations of the fossil material and to confirm the ability of the organisms to precipitate their shells in equilibrium with the environment. Secondly, to show how geochemical composition of water varies with depth considering previous paleoenvironmental models obtained from the facies analysis and the way of life of organisms, using innovative geochemical methods such as the study of carbon stable isotopes and rare earth elements plus yttrium in fossils. Finally, it aims to establish the reasons that produce variations in the geochemical composition of waters related to depth. In the present work, we present two case studies from contemporary marine successions deposited in different paleodepths: Arroyo Loncoche (Neuquén Basin; Fig. 1a) and Río Guanaco (Austral Basin; Fig. 1b). In both cases, paleodepths were defined based on the facies analysis and the way of life of organisms. The Arroyo Loncoche sedimentary section (Neuquén Basin) includes the complete succession of the Vaca Muerta and Chachao Formations (Fig. 2) and has been defined as ramp deposits that include different environments from basin to proximal middle ramp. The Chachao Formation is composed mainly of oyster biostromes of the genus Aetostreon sp. (Kietzmann et al., 2008, 2014; Kietzmann and Palma, 2009; Gómez Dacal et al., 2018). From the study of the way of life of oysters, Hernández-Ocaña et al. (2015) showed that this genus lived under shallow-water conditions, from the intertidal zone to 30 m depth maximum. The Río Guanaco sedimentary section of the Austral Basin is found in the southeastern area of the Santa Cruz Province, and includes the complete Springhill Formation and the lower member of the Río Mayer Formation (Fig. 2; Richiano et al., 2012). From the fossils and facies analyses, this sequence has been characterized as an external platform composed mainly of black shales, rich in belemnites of the Belemnopsis sp. fauna (Richiano et al., 2015). Jarvis (1980) postulates, that belemnites lived in depths between 120 and 330 m. A representative sedimentary succession of each study area was carried out, selecting the best and most complete outcrops of the formations (Fig. 3). In addition, a systematic analysis of the fossil material was made in order to stablish their petrographic (cathodoluminscence and scanning electron microscopy) and geochemical characteristics (rare earth elements and yttrium and stable isotopes of C and O). From cathodoluminescence and scanning electron microscopy studies it was possible to demonstrate that selected samples of Aetostreon sp. and Belemnopsis sp. were well preserved (Fig. 4). The REY results, obtained from belemnites, show that the Río Guanaco section contains higher HREY, Y/Ho ratios and the La and Eu anomalies than Arroyo Loncoche section (Fig. 5; Table 1). Oysters and belemnites precipitate their shells in equilibrium with the sea-water composition, where the difference in REY values recorded is attributed to the greater influence of continental sediment supply at the time of the formation of the oyster shells. Chemostratigraphic curves were obtained from the isotopic results (Fig. 6; Table 2). The curve of ?13C from the Río Guanaco section shows more negative values and less variations than the curve of the Arroyo Loncoche section (Fig. 6). This difference Is considered as response of the belemnites may have precipitated their shells under deeper environmental conditions, where the export of carbon from the surface to the deep ocean is continuous and generates an enrichment of 12C. From the results of the present study the following conclusions are obtained: • According to the way of life of the organisms and the interpreted environments in the sedimentary successions, we suggest that belemnites lived in a deeper marine environment, while oysters lived from the intertidal to the 30 m depth. • Both cathodoluminescence and scanning electron microscopy studies indicate a good preservation for selected samples of Aetostreon sp. and Belemnopsis The Río Guanaco section (Austral Basin) shows higher HREY values, Y/Ho rations and Eu and La anomalies than those recorded in Arroyo Loncoche (Neuquén Basin). These differences agree with the environmental conditions in relation to the continental sedimentary supply during the precipitation of the shells. • The chemostratigraphic curve from Río Guanaco section shows more negative and more homogeneous values than those recorded in the curve of Arroyo Loncoche section. This difference is attributed to belemnites having precipitated their shells in deeper environments, where the export of carbon from the surface to the deep ocean is continuous and generates an enrichment of 12C. • Isotopic and REY trends corroborate that belemnites from Austral Basin lived in a deeper marine environment than oysters from Neuquén Basin.